Communication, decision-making and the optimal degree of transparency of monetary policy committees - Anke Weber (Deutsche Bundesbank, 2008)
This paper develops a theoretical model of dynamic decision-making of a monetary policy committee with heterogeneous members. It investigates the optimal transparency, and the optimal way of transmitting information of committees, by analysing the effects different communication strategies have on financial markets. It is shown that the communication strategy of the central bank committee has a significant effect on the predictability of monetary policy decisions when there is asymmetric information between the committee and market agents. Transparency about the diversity of views of the committee surrounding the economic outlook makes future monetary policy more predictable. However, communicating the diversity of views regarding monetary policy decisions may lead to less predictability of monetary policy in the short term. In addition, it is shown that communication in the form of voting records has the greatest effect on market participants' near term policy expectations. These results support findings of the empirical literature and have strong implications for the optimal communication strategies of committees including the question whether individual voting records should be published.
Keywords: E52; E50; E58; 330; Monetary Policy Committees; Uncertainty; Communication; Transparency; Geldpolitik; Gruppenentscheidung; Staatliche Information; Informationsökonomik; Wirtschaftspolitische Wirkungsanalyse; Finanzmarkt; Zinsstruktur; Theorie